Foodborne Microbial Pathogens Mechanisms and Pathogenesis - Bhunia, Arun K.; SpringerLink (Online service) (New York, NY : Springer New York : Imprint: Springer, 2018)
This book primarily covers the general description of foodborne pathogens and their mechanisms of pathogenesis, control and prevention, and detection strategies, with easy-to-comprehend illustrations. The book is an essential resource for food microbiology graduate or undergraduate students, microbiology professionals, and academicians involved in food microbiology, food safety, and food defense-related research or teaching. This new edition covers the significant progress that has been made since 2008 in understanding the pathogenic mechanism of some common foodborne pathogens, and the host-pathogen interaction. Foodborne and food-associated zoonotic pathogens, responsible for high rates of mortality and morbidity, are discussed in detail. Chapters on foodborne viruses, parasites, molds and mycotoxins, and fish and shellfish are expanded. Additionally, chapters on opportunistic and emerging foodborne pathogens including Nipah virus, Ebola virus, Aeromonas hydrophila, Brucella abortus, Clostridium difficile, Cronobacter sakazakii, and Plesiomonas shigelloides have been added. The second edition contains more line drawings, color photographs, and hand-drawn illustrations.
Introduction to Foodborne Pathogens --  Biology of Bacterial Pathogens -- Host Defense against Foodborne Pathogens -- General Mechanism of Pathogenesis -- Animal and Cell Culture Models to Study Foodborne Pathogen -- Foodborne Viral Pathogens and Infective Protein -- Foodborne Parasites -- Molds and Mycotoxins -- Fish and Shellfish Toxins -- Staphylococcus aureus --  Bacillus cereus and Bacillus anthracis --  Clostridium botulinum, Clostridium perfringens, Clostridium difficile -- Listeria monocytogenes --  Escherichia coli -- Salmonella enterica -- Campylocbacter and Arcobacter -- Yersinia enterocolitica and Yersinia pestis -- Vibrio cholerae, Vibrio parahaemolyticus, and Vibrio vulnificus -- Shigella species -- Opportunistic and Emerging Foodborne Pathogens: Aeromonas hydrophila, Plesiomonas shigelloides, Cronobacter sakazakii, and Brucella abortus.
Keywords: Food -- Microbiology; Food science; Immunology; Food Microbiology; Food Science; Immunology